Waste Management: Descriptive Study in Nglurah Village, Karanganyar Regency - Pratama, Yogi Pasca; Samudro, Bhimo Rizky; Yogi, Anang Pra (LPPM of NAROTAMA UNIVERSITY, 2021)
The purpose of this study is to describe the work system and the concept of waste management in Nglurah Village, Tawangmangu, Karanganyar, Indonesia. The study also sought to find out the reasons underlying the formation of the Wagu Budoyo waste management group established by the community. This study is a qualitative study with a descriptive approach. Data collection is done by conducting interviews and observations. The results of this study provide a description of the establishment, work system and direction of development of the Wagu Budoyo waste management group, Nglurah Village, Tawangmang, Karanganyar Regency. It was found that there was a central role in art studios with central figures who could initiate various activities including community-based waste management. Keyword: Waste Bank, Waste Management JEL Classifications: O13, R11